(untitled) (Justicia &Derecho, 2023)
Lawyers’ professional behavior can be controlled by four different systems that use as motivation the fear of state sanction, the desire to accumulate wealth, the search for esteem and recognition, and the desire to act in accordance with morality. Along with identifying these four systems, this paper analyzes the causes that have produced the last two systems are not perceived today as instruments to guide professional conduct. Finally, it proposes strategies to allow its proper functioning.